The Development of Fallibilism in the Philosophy of Charles Peirce - Akelyan, Davit (Bulletin of Yerevan University E: Philosophy, Psychology, 2026)
The article examines the reasons, arguments, critiques of earlier epistemological positions, and the developmental tendencies of fallibilism in the philosophy of Charles Peirce. Peircean fallibilism is primarily the result of recognizing and attempting to overcome the limitations of the subject’s cognitive capacities and the methods of inquiry, which is most evident in Peirce’s critique of Cartesian dogmatic-fundamentalist views and methodological skepticism. It can be argued that the formation and development of Peirce’s fallibilism rest on three key principles: (1) the rejection of the method of universal and arbitrary doubt, (2) the acceptance of the requirement of moderate doubt grounded in sufficient reason, and (3) the renunciation of the demand for absolute epistemological foundations of knowledge and belief. Although this epistemological stance leads to the recognition of the fallibility of all knowledge and cognitive capacities, it reconceptualizes inquiry, and particularly scientific inquiry, as a communal and intersubjective dynamic process that can mitigate subjectivity and foster the growth of knowledge, while preventing the ossification of beliefs and knowledge within cognition. According to the author, Peirce’s fallibilism is a moderate epistemological position that avoids dogmatism, fundamentalism, infallibilism, and radical skepticism, thereby rejecting maximalist demands and conceptual limitations placed upon knowledge.
Keywords: Charles Peirce; fallibilism; dogmatism; fundamentalism; fallibility of knowledge; justification of knowledge; overcoming subjectivity; intellectual humility